(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2020)
This paper aim is to reconstruct the role or religion and spirituality in the history of the Third Reich in order to highlight a much more important issue. This issue is related to the implementation of an authoritarian pedagogy in which various tools are being used to instrumentalize the human subject. Therefore this paper highlights the most significant elements of the processes that had led to the emergence of Nazi ideology and the specific form of spirituality popularized by Nazi officials. The method used to achieve this goals is based on critical analysis of the educational aspect of the mentioned process.